Stereotactic Body Radiotherapy for Treatment of Squamous Cell Carcinoma of the Tongue Associated with Human Papilloma Virus: A Case Report - Rodgers, Brian C.; Neupane, Prakash; Lominska, Christopher; Shnayder, Yelizaveta (Frontiers in Oncology, 2013)
Stereotactic body radiotherapy has emerged as a treatment for recurrent squamous cell carcinoma of the head and neck in the field of prior radiation. We report a case of its use in an HPV positive patient with squamous cell carcinoma of the right base of tongue. The patient had complete response to treatment and modest toxicities were noted. This represents encouraging results that stereotactic body radiotherapy is also useful for salvage in patients with HPV positive disease.